Labor Contracts under Asymmetric Information when Workers are Free to Quit - Meyer, Margaret A. (Quarterly Journal of Economics, 1987)
This paper examines the impact of workers' ability to quit on the performance of labor contracts between workers and privately informed firms. While the need to induce workers to remain with the firm necessarily lowers total welfare, the effect on employment levels is to reduce the magnitude of the inefficiency due to asymmetric information, whether this inefficiency is under- or overemployment. The model predicts that employment distortions increase with the strength of lock-in effects on workers, a prediction which contrasts with the results of efficiency wage models and which may help in empirical testing of labor contract theory.